Irrational Behavior of Investors and Its Risk to Their Returns: Evidence from Chinese Mutual Funds - Fan, Han (2022)
With the development of Chinese economy and maturation of China fund market, actively managed mutual funds are gradually becoming an important investing instrument for both retail and institutional investors. Although on average the funds’ performance is satisfying, irrational behavior is still a risk prevent investors from realizing profit.